IMPLEMENTASI LESSON STUDY UNTUK MENINGKATKAN KINERJA DOSEN PENDIDIKAN MATEMATIKA FKIP UNIVERSITAS MUHAMMADIYAH METRO - Rahmad Bustanul Anwar; Dwi Rahmawati (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2015)
In higher education need to apply the process of teaching, coaching, and training both to students. Implementation of teaching, coaching, and training should be conducted in a professional manner because students are required ready to plunge into human society as an adult, responsible and forward-minded. Three aspects should be offset by improved performance in designing devices lecturer and the learning process. One effective way to improve the quality of learning undertaken by lecturers is to implement Lesson Study is designed so well that it will make a professional and innovative faculty. Lesson study is a vehicle for the development of the faculty, where the target is learning to the learning process. The purpose of this research is to improve the quality of teaching faculty of mathematics education through lesson study that starts from perancanaan, implementation and evaluation of learning. As well as provide learning among fellow faculty of mathematics education, especially the development of new lecturer to senior lecturer to student learning. Subjects in this study 4 dilakanakan professor of mathematics education in four subjects. The conclusion from this study is the implementation of lesson study activities can increase the performance of the education faculty of mathematics at the lecture. This is shown by research that showed an increase from cycle I to cycle II. Although there are some indicators that are not increasing but still in good category